Control of Haematobia irritans in the Minas Gerais Semiarid - Costa, Evely Giovanna Leite; Carneiro, Juliana Campos; Bastos, Gabriela Almeida; Vasconcelos, Viviane de Oliveira; Souza, Rogério Marcos de; Almeida, Anna Christina de; Duarte, Eduardo Robson (Acta Scientiae Veterinariae, 2016)
Background: Beef cattle is considered to be one of the most important economic activities, however, it presents problems in the production chain such as the occurrence of parasites that reduce the growth, performance, productivity and may cause mortalities occasionally. The chemical control is the most used alternative to reduce ectoparasites. Nevertheless, inappropriate management of insecticides has contributed to the selection of population resistant to the products available on the market. This paper aimed to evaluate the practices of management and the application of insecticides used to control horn flies in farms of dairy cattle in the North of the state of Minas Gerais. Materials, Methods & Results: It was visited 62 rural properties, which produce milk. Semi-structured questionnaires were applied in order to obtain information on the characteristics of the properties (location, size and type of the cattle), on the knowledge about the epidemiology of the horn flies, and on the practices adopted to the control of those parasites. The practices adopted include the moment of application of the insecticides, frequency of the cattle treatment, used products, method of application, number of animals treated, and choice and substitution criteria of insecticides. The data collected were tabulated in contingency tables, and they were analyzed using the chi-square test, considering a significance of 5%. The racial composition of the cattle in the farms was mainly mixed-race of unknown origin, representing 77% of the animals evaluated. In this research, it was reported a greater incidence of horn flies infestation on adult beef herd, and 23.6% of the producers reported occurrences of infestation in the whole herd, not differing by categories. The infestation peaks of the fly occurred from November to March. It was also found a greater frequency of pyrethroid use in the region (P < 0.001), where 43.1% of the producers used associations of pyrethroid or organophosphate to control the flies, high efficiency being reported. From the properties assessed, 92% presented inadequacy in the practices of control of horn flies, for instance, the lack of using cattle manure tank, the accumulation of open waste, the lack of rotation of insecticides, which can favor the selection of resistant flies. Discussion: In this paper, it was reported 77.19% of predominance of Haematobia irritans infestation from November to March mainly in animals with a higher percentage of European or mixed-race genetics. Such results corroborate with the literature, because it was verified the influence of race and hair color in the level of infestation in the animals, although, in the same race, each individual presents different susceptibilities. Taurine beef cattle are more susceptible to infestation by horn flies than zebu cattle. Thus, the lower the proportion of zebu cattle genetics in the herd, the greater the infestation. Taurine beef cattle are more infested because shows a greater number of sebaceous glands and greater concentration of testosterone being attractive before the calves castrated, cows, and after, young animals. Cypermethrin was predominant in most part of the commercial insecticides used in the properties to control this ectoparasite, which could be justified by the large number of products available on the market with such compound in the formulations. The high efficiency of the associations of the insecticides reported by the producers could justify itself by the presence of active ingredients with different mechanisms of action. However, the limitation on the use of these associations is that not always the chemical compounds contained in the drug act simultaneously, being able to favor the selection of parasites resistant to different insecticides present in these formulations.